2021
DOI: 10.1007/s11548-020-02295-9
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based radiomic feature analysis of end-stage liver disease for severity stratification

Abstract: Purpose We aimed to develop a predictive model of disease severity for cirrhosis using MRI-derived radiomic features of the liver and spleen and compared it to the existing disease severity metrics of MELD score and clinical decompensation. The MELD score is compiled solely by blood parameters, and so far, it was not investigated if extracted image-based features have the potential to reflect severity to potentially complement the calculated score. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In a recent study by Nitsch et al, magnetic resonance imaging (MRI)-based radiomic features and random forest classifier were used to predict the severity of liver cirrhosis, with clinical decompensation and model for end-stage liver disease (MELD) scores as reference standard. Nitsch et al concluded that adding splenic MRI-based radiomic features can increase the AUC for predicting a higher median MELD score or clinical decompensation [ 24 ]. However, their study lacked an objective reference standard and was only focused on patients with known cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Nitsch et al, magnetic resonance imaging (MRI)-based radiomic features and random forest classifier were used to predict the severity of liver cirrhosis, with clinical decompensation and model for end-stage liver disease (MELD) scores as reference standard. Nitsch et al concluded that adding splenic MRI-based radiomic features can increase the AUC for predicting a higher median MELD score or clinical decompensation [ 24 ]. However, their study lacked an objective reference standard and was only focused on patients with known cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Feature analysis was performed on the contrast-enhanced imaging acquisition [ 17 ]. Due to the homogenous imaging conditions described above, we did not apply any kind of pre-processing such as re-sampling or other normalization.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the homogenous imaging conditions described above, we did not apply any kind of pre-processing such as re-sampling or other normalization. Liver and spleen images were segmented using a U-net-based network architecture successively trained on expert segmentations [ 17 , 19 ]. The PyRadiomics library (version 2.0.1) [ 20 ] was used to extract 1288 features each from the liver and spleen, resulting in a total of 2577 imaging features (including a size ratio).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the association of tumor genetic heterogeneity in HN cancer with patients’ prognoses, it was concluded that higher heterogeneity is related to worse outcomes [ 6 , 7 , 8 ]. This genetic heterogeneity can lead to imaging heterogeneity, which can be quantified by radiomics [ 9 ] on 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) images [ 10 , 11 ]. The feasibility of conventional PET/CT features for risk assessment in patients with HN cancer has been extensively investigated [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%